2011
DOI: 10.1016/j.neurobiolaging.2009.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Five out of 16 plasma signaling proteins are enhanced in plasma of patients with mild cognitive impairment and Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a progressive neurodegenerative disorder with characteristic neuropathological changes of the brain. Great efforts have been undertaken to determine the progression of the disease and to monitor therapeutic interventions. Especially, the analysis of blood plasma had yielded incongruent results. Recently, Ray et al. (Nat. Med. 13, 2007, 1359f) identified changes of 18 signaling proteins leading to an accuracy of 90% in the diagnosis of AD. The aim of the present study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 0 publications
7
91
2
Order By: Relevance
“…In our study, we found reduced levels of MIP-1d in monocytes, but enhanced MIP-1d levels in plasma. These data support similar results obtained by Marksteiner et al [112] (2011) [132] .…”
Section: Cytokines and Chemokinessupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, we found reduced levels of MIP-1d in monocytes, but enhanced MIP-1d levels in plasma. These data support similar results obtained by Marksteiner et al [112] (2011) [132] .…”
Section: Cytokines and Chemokinessupporting
confidence: 93%
“…BACE cleaves APP and releases a large N-terminal fragment (sAPPβ). The membrane-anchored frag- [73,75] Decreased [65] β-amyloid (Aβ) Decreased [45,46] No difference [79][80][81][82] No difference [47] Aβ1- 40 No difference [24] No difference [83] Increased [84] Decreased [85] Aβ1- 42 Decreased [24] Increased [83] -Aβ1-42/Aβ1-40 ratio Decreased [48] No difference [83] Decreased [78,84,86] APP ratio --Decreased [90][91][92][93] Ubiquitin Increased [24] No difference [148] BACE1 Increased [67] --Cholesterol -Decreased [94,95] Increased [96][97][98] 24S-hydroxycholesterol Increased [102] No difference [103] Decreased [104] Homocysteine -Increased [106,107,109] Epidermal growth factor -Decreased [111] Decreased [93] Increased [112] Glial cell line-derived growth factor -Decreased [111] No difference …”
Section: Aβ1-42mentioning
confidence: 99%
See 2 more Smart Citations
“…CCL, chemokine that contains a C-C motif; CXCL, chemokine that contains a C-X-C motif; G-CSF, granulocyte-colony stimulating factor; GDNF, glialderived neurotrophic factor; ICAM-1, intercellular adhesion molecule-1; IGFBP-1, insulin-like growth factor-binding protein-6; IL, interleukin; PDGF-BB, platelet-derived growth factor BB; TRAIL-R4, TNF-related apoptosis-inducing ligand receptor-4 [15]. Some of these results were verified independently, showing an increased concentration in Biocoll isolated plasma of 5 out of these proteins in MCI and AD patients compared to healthy subjects: EGF, GDNF and MIP1δ (in AD), MIP4 (in MCI), and RANTES (in MCI and AD) [16].…”
Section: Blood Biomarkersmentioning
confidence: 87%